Factors Affecting the Level of Understanding of Introductory Accounting Courses - Annisa, Dea; Utami, Tri; Anggraini, Dila (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2025)
This lesson wants to explore each contribution from each aspect that has been determined to be studied as a problem topic to be discussed from this study. This lesson was held at Pamulang University, Undergraduate Accounting Study Program, 2nd semester, Faculty of Economics and Business, located at Surya Kencana No. 1, West Pamulang, Pamulang District, South Tangerang City, Banten. The sample was selected from the Slovin formula, which was found to be 1,639 students from a total of 394 observation reports and using associative quantitative techniques. For the analysis of multiple linear regression. The lesson shows that the infrastructure of learning origins contributes to the level of introductory accounting lesson deepening. Teacher skills do not contribute to the level of introductory accounting lesson deepening. Locus of control is able to moderate the learning infrastructure. Locus of control is unable to moderate the origin and learning skills.